Addition of magnesium sulfate to intraperitoneal ropivacaine for perioperative analgesia in canine ovariohysterectomy - Gomes, Denis R.; Nicácio, Isabela P. G. A.; Cerazo, Letícia M. L.; Dourado, Larissa; Teixeira-Neto, Francisco J. [UNESP]; Cassu, Renata N. (Wiley, 2020)
Magnesium may be used as an adjunctive analgesic for perioperative pain management because of its antinociceptive properties. This study investigated the analgesic efficacy of intraperitoneal ropivacaine combined with magnesium sulfate in canine ovariohysterectomy. Forty-five dogs sedated with acepromazine/meperidine and anesthetized with propofol/isoflurane were randomly distributed into three treatments, administered intraperitoneally (n = 15 per group): saline solution (group S), 0.25% ropivacaine (3 mg/kg) alone (group R), or in combination with magnesium sulfate (20 mg/kg, group R-Mg). Intravenous fentanyl was given to control cardiovascular responses to surgical stimulation. Postoperative pain was assessed using an Interactive Visual Analog Scale (IVAS), the short form of the Glasgow Composite Pain Scale, and mechanical nociceptive thresholds. Morphine/meloxicam was administered as rescue analgesia. Intraoperatively, the R-Mg group required less fentanyl (p =.02) and exhibited higher incidence of hypotension (systolic arterial pressure <90 mm Hg, p =.006) compared with the S group. Lower IVAS pain scores were recorded during the first hour in the R-Mg group than the other groups (p =.007–.045). Postoperative rescue analgesia did not differ between groups. Intraperitoneal magnesium sulfate administration, in spite of decreasing intraoperative opioid requirements, increased the incidence of hypotension with minimal evidence of postoperative analgesic benefits.
Keywords: analgesia; canine; intraperitoneal; local anesthetic; NMDA receptor antagonist